Portfolio Complexity and Herd Behavior: Evidence from the German Mutual Fund Market - Alexander Franck; Andreas Walter (Kredit und Kapital, 2012)
Portfolio Complexity and Herd Behavior: Evidence from the German Mutual Fund Market We examine the herd behavior among equity funds in Germany based on a large sample of funds from 2000 to 2009. We show that a large portion of the detected herding can be explained by identical trading among funds of the same investment company. However, we also find statistically significant stock herding among funds belonging to different fund families. In contrast to existing herding studies which analyze herd behavior within a purely national stock environment, we investigate mutual fund herding in international stocks. We contribute to the literature by analyzing the impact of portfolio complexity on herd behavior. We find the most pronounced levels of herding for funds choosing their portfolio stocks from a broad, international and therefore complex investment universe. Further, we approximate a fund's portfolio complexity by its size and find high levels of herding among the biggest funds. To analyze the herd behavior of individual funds, we introduce a new and intuitive way to assign levels of herding to funds according to their trading activity within a given period. We show that managers differentiate between buy-herding and sell-herding and that individual funds exhibit similar herding intensities within a given and a succeeding period. (JEL D82, G11, G23) – – Portfolio-Komplexität und Herdenverhalten: Erkenntnisse aus dem deutschen Investmentfonds-Markt Wir untersuchen das Herdenverhalten von deutschen Aktienfonds anhand einer großen Fonds-Stichprobe für die Jahre 2000 bis 2009. Wir zeigen, dass ein großer Anteil des aufgezeigten Herdenverhaltens durch identische Handelsentscheidungen von Fonds der gleichen Investmentgesellschaft erklärt werden kann. Jedoch finden wir auch statistisch signifikantes Herdenverhalten bei Fonds von verschiedenen Fondsgesellschaften. Im Gegensatz zu existierenden Studien, die Herdenverhalten ausschließlich innerhalb nationaler Aktienmärkte analysieren, untersuchen wir auch das Herdenverhalten innerhalb internationaler Aktienmärkte. Wir erweitern die Literatur durch unsere Analysen hinsichtlich des Einflusses der Portfolio-Komplexität auf Herdenverhalten. Wir finden die höchsten Maße für Herdenverhalten für Aktienfonds, die in großen, internationalen und daher komplexen Märkten investieren. Des Weiteren approximieren wir die Portfolio-Komplexität durch die jeweilige Fondsgröße und entdecken eine starke Herden-Ausprägung bei den größten Fonds. Um das Herdenverhalten von einzelnen Fonds innerhalb verschiedener Perioden zu analysieren, führen wir eine neue und intuitive Methodik ein. So können wir zeigen, dass sich das Herdenverhalten der Fonds-manager bei Kauf- und Verkaufsentscheidungen unterscheidet und dass individuelle Fonds auch in der nächsten Periode ähnliche Herdenstrategien verfolgen.
Keywords: D82; G11; G23; 330